A. V. Dicey and English constitutionalism. Issue 1 (2nd January 2019) - Kirby, James
ABSTRACT: The jurist A. V. Dicey's study of the Law of the Constitution (1885) has been since its publication the dominant analysis of the British constitution and the source of orthodoxy on such subjects as parliamentary sovereignty and the rule of law. This canonical status has obscured the originality of Dicey's ideas in the history of legal and political thought. Dicey reworked the traditional idea of sovereignty into two separate concepts – legal and political sovereignty – in order to square the common law notion of the sovereignty of parliament with the democratic idea of the sovereignty of the people. He forged a new concept – 'the rule of law' – to explain the legal basis of liberty in common law countries in a manner that was both Benthamite and constitutionalist. Finally, he provided a democratic and anti-federalist rationale for maintaining the Union of Great Britain and Ireland. This majoritarian, centralist and utilitarian constitutionalism has been one of the most enduring products of Victorian scholarship. This article seeks to recover it in its original context and, in so doing, to show the value of reintegrating legal thought into the mainstream of modern British history and the history of political thought.